The effects of desiccation crack and seasonal variation on hydrological response of compact clay embankment - Arwan Apriyono; Yuliana Yuliana; Viroon Kamchoom‬; Anthony Kwan Leung; Apiniti Jotisankasa (Canadian Geotechnical Journal, 2025)
The presence of cracks significantly impacts the hydrological behaviour of clay embankments. This study aimed to enhance understanding of the complex interplay between the amount and propagation of desiccation cracks and seasonal variations. A full-scale embankment was constructed and equipped with an array of instruments, including pore water pressure, volumetric water content (VWC), and crack observer. The results suggested that continues cracks at shallow depths (0.5 m) exhibit significant seasonal fluctuations due to pronounced soil–atmosphere interactions, facilitating rapid water movement and substantial changes in crack width. In contrast, discontinuous cracks at intermediate depths (0.5 m) are less affected by seasonal changes, but they can propagate and connect over time due to repeated wetting and drying cycles. The crack intensity factor (CIF) above 0.4 m is highly sensitive to climatic variations, leading to pronounced fluctuations with changes in rainfall and dry conditions. The twofold increase in CIF values leads to a significant reduction in VWC (by 13.5%) at the depth of 0.25 m under the same atmospheric water balance. However, this effect is less pronounced at greater depths, such as 0.5 m, as discontinuous cracks are less effective in facilitating rapid drainage and moisture loss.
Keywords: Soil and Unsaturated Flow; Landslides and related hazards; Soil Moisture and Remote Sensing